NusG inhibits RNA polymerase backtracking by stabilizing the minimal transcription bubble - Matti Turtola; Georgiy A Belogurov (eLife Sciences Publications Ltd., 2022)
Universally conserved factors from NusG family bind at the upstream fork junction of transcription elongation complexes and modulate RNA synthesis in response to translation, processing, and folding of the nascent RNA. Escherichia coli NusG enhances transcription elongation in vitro by a poorly understood mechanism. Here we report that E. coli NusG slows Gre factor-stimulated cleavage of the nascent RNA, but does not measurably change the rates of single nucleotide addition and translocation by a non-paused RNA polymerase. We demonstrate that NusG slows RNA cleavage by inhibiting backtracking. This activity is abolished by mismatches in the upstream DNA and is independent of the gate and rudder loops, but is partially dependent on the lid loop. Our comprehensive mapping of the upstream fork junction by base analogue fluorescence and nucleic acids crosslinking suggests that NusG inhibits backtracking by stabilizing the minimal transcription bubble.